Developmental and contextual risks of social physique anxiety among female athletes - Gay, J. L.; Monsma, E. V.; Torres-McGehee, T. M. (Research Quarterly for Exercise and Sport, 2011)
In the present study, we examined developmental and contextual factors that may increase the odds of reporting higher social physique anxiety (SPA) among 404 adolescent athletes 11 to 16 years old. Findings showed older, later maturing athletes past peak height velocity and with greater body mass index (BMI) reported higher SPA. Individual aesthetic sport athletes were older at menarche, had lower BMI, and reported higher SPA. The odds of reporting higher SPA were 4.5 times higher (odds ratio = 4.61) for individual aesthetic sport athletes than for nonaesthetic sport athletes. Team aesthetic sport contexts were not implicated in SPA risk. Results are discussed in terms of self-selection away from individual aesthetic sports and the relevance of physical size and puberty in the SPA construct.